The Clinical and Imaging Characteristics Associated With Neurological Sequelae of Pediatric Patients With Acute Necrotizing Encephalopathy - Zhu, Hong-Min; Zhang, Si-Min; Yao, Cong; Luo, Meng-Qing; Ma, Hui-Jing; Lei, Tao; Yuan, Chun-Hui; Wu, Ge-Fei; Hu, Jia-Sheng; Cai, Chun-Quan; Liu, Zhi-Sheng (Frontiers in Pediatrics, 2021)
Background: Acute necrotizing encephalopathy of childhood (ANE) is a rare but rapidly progressing encephalopathy. And importantly, the exact pathogenesis and evidence-based treatment is scarce. Thus, we aimed to identify the clinical, imaging and therapeutic characteristics that associated with prognosis of pediatric ANE patients. Methods: A retrospective study was conducted on pediatric patients with ANE who admitted to Wuhan Children's Hospital between January 2014 and September 2019. All cases met the diagnostic criteria for ANE proposed by Mizuguchi in 1997. The clinical information and follow-up data were collected. The prognostic factors were analyzed by trend Chi-square test and Goodman-Kruskal Gamma test. Results: A total of 41 ANE patients ranging in age from 8.9 to 142 months were included in this study. Seven cases (17 %) died and the other 34 survivors had different degrees of neurological sequelae. Factors tested to be significantly correlated with the severity of neurological sequelae were the intervals from prodromal infection to acute encephalopathy (G=-0.553), conscious disturbance (r=0.58), endotracheal intubation (r=0.423), elevation of alanine aminotransferase (r = 0.345), aspartate aminotransferase (r = 0.393) and cerebrospinal fluid protein (r =0.490). In addition, dynamic Magnetic Resonance Imaging (MRI) evaluation in follow-up revealed that the total numbers of brain lesion location (χ^2=6.29，P<0.05), hemorrhage (r = 0.580), cavitation (r=0.410) and atrophy (r=0.602) status were significantly correlated with the severity of neurological sequelae, while early steroid therapy (r=-0.127 and 0.212, respectively) and IVIG (r =0.111 and -0.023, respectively) within 24h or within 72h after onset were showed no association. Conclusions: Intervals from prodromal infection to acute encephalopathy (≤one day), total numbers of brain lesion location (≥ three), the recovery duration of hemorrhage and atrophy (>three months), the presence of cavitation predict severe neurological sequelae in pediatric patients with ANE. Early treatments, including steroid therapy and IVIG, had no correlation with better outcomes. Further studies are needed to establish a consensus guideline for the management of ANE.